Prevalence, Colonization, Epidemiology, and Public Health Significance of Clostridioides difficile in Companion Animals - Hernandez, Belen G.; Vinithakumari, Akhil A.; Sponseller, Brett; Tangudu, Chandra; Mooyottu, Shankumar (Frontiers in Veterinary Science, 2020)
Clostridioides difficile, previously Clostrdium difficile, is a major cause of antibiotic-associated enteric disease in humans in hospital settings. Increased incidence of C. difficile infection (CDI) in community settings raises concerns over an alternative source of CDI for humans. The detection of genetically similar and toxigenic C. difficile isolates in companion animals, including asymptomatic pets, suggests the potential role of household pets as a source of community-associated CDI. The close association between companion animals and humans, in addition to the use of similar antibiotics in both species, could provide a selective advantage for the emergence of new C. difficile strains and thus increase the incidental transmission of CDI to humans. Therefore, screening household pets for C. difficile is becoming increasingly important from a public health standpoint and may become a part of routine testing in the future, for the benefit of susceptible or infected individuals within a household. In this review, we analyze available information on prevalence, pathophysiology, epidemiology, and molecular genetics of C. difficile infection, focusing on companion animals and evaluate the risk of pet-borne transmission of CDI as an emerging public health concern. Molecular epidemiological characterization of companion animal C. difficile strains could provide further insights into the interspecies transmission of CDI. The mosaic nature of C. difficile genomes and their susceptibility to horizontal gene transfer may facilitate the inter-mixing of genetic material, which could increase the possibility of the emergence of new community-associated CDI strains. However, detailed genome-wide characterization and comparative genome analysis are warranted to confirm this hypothesis.